2009
DOI: 10.1038/modpathol.2008.141
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the World Heath Organization classification criteria for the diagnosis of systemic mastocytosis in bone marrow

Abstract: In the World Health Organization classification, one major and four minor criteria are specified for the diagnosis of systemic mastocytosis. We report our experience using these criteria to diagnose systemic mastocytosis involving bone marrow. A total of 59 patients with clinically suspected systemic mastocytosis underwent comprehensive bone marrow examination, including immunophenotyping by immunohistochemistry and/or flow cytometry and molecular studies for KIT exon 17 mutations. Serum tryptase levels were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0
5

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 23 publications
3
35
0
5
Order By: Relevance
“…Undoubtedly, the WHO criteria represented a major step forward in both the diagnosis and classification of mastocytosis, contributing to the distinction between good-(eg cutaneous mastocytosis and indolent systemic mastocytosis) vs poor-prognosis subgroups (eg aggressive systemic mastocytosis, mast cell leukemia). However, since the initial proposal, only one study based on 59 patients 19 has prospectively evaluated the WHO criteria. Interestingly, preliminary data from this study indicate that based on the WHO criteria, some patients suffering from a true systemic mastocytosis cannot be classified as such.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Undoubtedly, the WHO criteria represented a major step forward in both the diagnosis and classification of mastocytosis, contributing to the distinction between good-(eg cutaneous mastocytosis and indolent systemic mastocytosis) vs poor-prognosis subgroups (eg aggressive systemic mastocytosis, mast cell leukemia). However, since the initial proposal, only one study based on 59 patients 19 has prospectively evaluated the WHO criteria. Interestingly, preliminary data from this study indicate that based on the WHO criteria, some patients suffering from a true systemic mastocytosis cannot be classified as such.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed the relative values of traditional morphologic criteria (ie major criterion) and the results of ancillary testing (ie minor criteria), suggesting that the WHO system is neither completely sensitive nor specific for systemic mastocytosis. 19 Here, we prospectively evaluate the utility of different clinical, biological, immunophenotypical, and molecular features of the disease (including all WHO major and minor diagnostic criteria), in a cohort of 133 patients uniformly diagnosed and followed at the Spanish Network on Mastocytosis (REMA). Based on our findings, a new algorithm is proposed, which may contribute to improve refined diagnosis and classification of mastocytosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies specific for tryptase and CD117 are most widely used and are useful for highlighting mast cells; however, neither antibody can distinguish benign from neoplastic mast cells. 2,3 Aberrant expression of CD2 or CD25 by mast cells in the bone marrow is more useful diagnostically because both antigens are often expressed by neoplastic mast cells but are not expressed in normal or reactive mast cells. 4,5 Therefore, assessment of CD2 and CD25 in the bone marrow is a potentially useful approach to establish the diagnosis of SM in the bone marrow.…”
mentioning
confidence: 99%
“…In earlier studies, 2,5,8 flow cytometry immunophenotypic analysis has been used to assess cases of SM. In one study, authors concluded that flow cytometry immunophenotyping was more sensitive than histology combined with immunohistochemistical analysis for detecting bone marrow involvement.…”
mentioning
confidence: 99%